2013
DOI: 10.1177/1741143213494891
|View full text |Cite
|
Sign up to set email alerts
|

Critical practice leadership in post-compulsory education

Abstract: This article questions why leaders in post-compulsory education tend not to view leadership research positively or utilise it in improving their practice. Drawing on the theoretical literature of educational management and leadership, and the current political and economic context of post-compulsory education, it proposes a new direction of critical practice leadership informed by advanced practitioner research. Challenging assumptions about leadership practice and leadership research creates opportunity for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Leadership in schools in England has drawn the attention of a number of researchers during the current century and has been dominated by numerous concepts, styles and models of what is perceived to be effective leadership (Moore et al 2002;Harris 2003Harris (a), 2003Harris (b), 2009Day, 2005;Murphy, 2010;Bush 2011Bush , 2012Bush and Crawford, 2012;Smith, 2013;Hammersley-Fletcher, 2015;Elliot, 2015). In an earlier study Bensimon et al (1989) suggested that the leadership literature and research is dominated by six leadership models: trait theory, behavioural theory, power and influence theory, contingency theory, cognitive theory and cultural/symbolic theory.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership in schools in England has drawn the attention of a number of researchers during the current century and has been dominated by numerous concepts, styles and models of what is perceived to be effective leadership (Moore et al 2002;Harris 2003Harris (a), 2003Harris (b), 2009Day, 2005;Murphy, 2010;Bush 2011Bush , 2012Bush and Crawford, 2012;Smith, 2013;Hammersley-Fletcher, 2015;Elliot, 2015). In an earlier study Bensimon et al (1989) suggested that the leadership literature and research is dominated by six leadership models: trait theory, behavioural theory, power and influence theory, contingency theory, cognitive theory and cultural/symbolic theory.…”
Section: Introductionmentioning
confidence: 99%
“…The last 10 years (2011-2020) represent 91.95% of all articles. In this period, 833 (40.87%) are set in the social context and address various issues, such as human resource management [81,82], organizational culture [79,83], social entrepreneurship [84,85], knowledge management [86], social learning [87], health care [88,89], social responsibility [77], education [90][91][92][93], and others. Around 26.7% of studies address the economic dimension in this period, highlighting the topics of performance [93][94][95], innovation [96,97], entrepreneurship [98], competitiveness [99,100], supply chains [101][102][103], and others.…”
Section: Qualitative Content Analysismentioning
confidence: 99%
“…Thus, educational leadership is deeply rooted in ethical practices that are embedded in a social context. According to Elliott (2015), research into leadership practices creates an opportunity for an ethical and practical perspective among leadership practitioners. Studies have shown that both parents and teachers expect educational leaders to utilise ethical decision-making processes in their work and when operating with others in teams, which is how the majority of contemporary school leadership activities are conducted (Branson and Gross, 2014; Grootenboer and Hardy, 2017; Shapiro and Stefkovich, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%